Design and Screening of a Glial Cell-Specific, Cell Penetrating Peptide for Therapeutic Applications in Multiple Sclerosis - Heffernan, Corey (Public Library of Science, 2012)
Multiple Sclerosis (MS) is an autoimmune, neurodegenerative disease of the central nervous system (CNS) characterized by demyelination through glial cell loss. Current and proposed therapeutic strategies to arrest demyelination and/or promote further remyelination include: (i) modulation of the host immune system; and/or (ii) transplantation of myelinating/stem or progenitor cells to the circulation or sites of injury. However, significant drawbacks are inherent with both approaches. Cell penetrating peptides (CPP) are short amino acid sequences with an intrinsic ability to translocate across plasma membranes, and theoretically represent an attractive vector for delivery of therapeutic peptides or nanoparticles to glia to promote cell survival or remyelination. The CPPs described to date are commonly non-selective in the cell types they transduce, limiting their therapeutic application in vivo. Here, we describe a theoretical framework for design of a novel CPP sequence that selectively transduces human glial cells (excluding non-glial cell types), and conduct preliminary screens of purified, recombinant CPPs with immature and matured human oligodendrocytes and astrocytes, and two non-glial cell types. A candidate peptide, termed TD2.2, consistently transduced glial cells, was significantly more effective at transducing immature oligodendrocytes than matured progeny, and was virtually incapable of transducing two non-glial cell types: (i) human neural cells and (ii) human dermal fibroblasts. Time-lapse confocal microscopy confirms trafficking of TD2.2 (fused to EGFP) to mature oligodendrocytes 3–6 hours after protein application in vitro. We propose selectivity of TD2.2 for glial cells represents a new therapeutic strategy for the treatment of glial-related disease, such as MS.